The Archetype of Medium and Large Organization Structure and Its Simplicity - Magdalena HOPEJ-TOMASZYCKA; Marian HOPEJ (Communications of International Proceedings, 2020)
The article addresses the organizational structure archetype as a solution to a dual problem adopted by the management of an organization at the second "top" level of the organizational hierarchy, i.e., on the one hand, organizational differentiation, and organizational integration on the other. An attempt is then made to define the features of the archetype of medium and large size organizations shaped according to the principle of simplicity. The final part presents the findings regarding the change of the archetype of the organizational structure.
Keywords: Management; Organizational Structure; Archetype; Simplicity.